2020
DOI: 10.1016/j.isci.2020.101844
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA (cfDNA) and Exosome Profiling from a Year-Long Human Spaceflight Reveals Circulating Biomarkers

Abstract: Summary Liquid biopsies based on cell-free DNA (cfDNA) or exosomes provide a noninvasive approach to monitor human health and disease but have not been utilized for astronauts. Here, we profile cfDNA characteristics, including fragment size, cellular deconvolution, and nucleosome positioning, in an astronaut during a year-long mission on the International Space Station, compared to his identical twin on Earth and healthy donors. We observed a significant increase in the proportion of cell-free mitoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 78 publications
6
29
0
Order By: Relevance
“…Consequently, our findings led to a profound revision of previous assumptions regarding the significance of the cir-mtDNA amounts detected in our and other previous works (10,34,51,55,59,6971). First, it can no longer be considered valid to examine cir-mtDNA with WGS or to discuss cir-mtDNA fragmentation under 1000 bp when discussing the overall cir-mtDNA population, since it accounts for a very tiny part of the cir-mtDNA amount.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Consequently, our findings led to a profound revision of previous assumptions regarding the significance of the cir-mtDNA amounts detected in our and other previous works (10,34,51,55,59,6971). First, it can no longer be considered valid to examine cir-mtDNA with WGS or to discuss cir-mtDNA fragmentation under 1000 bp when discussing the overall cir-mtDNA population, since it accounts for a very tiny part of the cir-mtDNA amount.…”
Section: Discussionsupporting
confidence: 75%
“…Note, other circulating nucleic acid species include viral, bacterial and fungal DNA or RNA. These whole types of circulating nucleic acids are now accurately characterized by high throughput sequencing (6,25,34,38,50,51). Despite previous efforts at designing methods, particularly Q-PCR based, for detecting mtDNA from blood cells (13,14,15,20), the standardization of cir-mtDNA quantification has proved to be a challenge, in particular concerning the issue of calibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the demonstrated contribution of CD14 + monocytes to increases in the circulating miRNAs, it is also possible that the miRNAs could be coming from another organ where they are more abundantly expressed. Thus, further studies will be necessary to determine the exact origin of the increased miRNAs and tissue response, such as with cell-free DNA profiling (Bezdan et al, 2020), which will be beneficial for mapping and developing effective countermeasures. Finally, the successful prevention of vascular damage through antagomir therapy in our proof-of-concept human tissue model demonstrates the need for further experiments to fully characterize antagomir therapies in vivo to understand their clinical safety and efficacy and to examine which components of the spaceflight miRNA signature make effective targets for antagomir therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, mitochondria, by generating mitochondrial ROS during cellular respiration, contribute to an increase in oxidative stress. Different studies have demonstrated that OsaD has a significant impact on human physiology as the changes in oxidative levels of irradiated cells may remain for days after exposure leading to long-term effects [ 38 ] in addition to serving as a plasma biomarker [ 39 ].…”
Section: Oxidative Stress and Damage (Osad) Generation In The Space Environmentmentioning
confidence: 99%